Pemberdayaan Wanita Tani dalam Penerapan Low External Input and Sustainable Agriculture (LEISA) untuk Rumah Pangan Lestari di Kecamatan Cibeureum - Sri Lestari; Muhammad Tassim Billah; Dedy Kusnadi (Fakultas Pertanian, Universitas Timor, 2021)
Empowerment of women farmers is one of the keys to success that affects the economic pace of farming families. Through the aim of the sustainable food house movement in synergy with the application of the LEISA concept, it is possible to optimize local resources and combine various components in an environmentally friendly farming system. Facts on the ground state that 33.5% of women farmers do not understand the importance of using inputs from within. This study was conducted to describe the empowerment of women farmers and to analyze the factors that influence the empowerment of women farmers as well as to develop strategies to improve the empowerment of women farmers in the application of LEISA for sustainable food houses. Data collection was carried out from April to June 2021. The research sample amounted to 53 people spread over 3 selected Kelurahan. The data in this study consisted of primary data and secondary data. Data analysis used descriptive analysis and multiple linear regression analysis. The conclusion of the study shows that the empowerment of women farmers assessed based on knowledge, attitudes and skills is in the moderate category, while the derivative effect of the dependent variable is influenced by the characteristics of women farmers, biophysical aspects, support for extension services and external factors which mean that women farmers need to be guided and directed synergy as a goal in achieving increased knowledge, attitudes and skills in supporting the implementation of LEISA for sustainable food houses. Strategies to increase women's empowerment in implementing LEISA for sustainable food houses can be done through 1) women's ability to make decisions, 2) use local resources, 3) increase support for extension services, and 4) provide relevant information sources and local government support. in achieving environmentally friendly sustainabl agriculture.